Reconstructing Indonesian Fiscal Policy for Sustainable National Electricity: A Quintuple Helix Perspective - Tambunan, Maria R.U.D (UI Scholars Hub, 2018)
The article aims at examining current Indonesian fiscal policy against its goals a possibility of its revitalization to support the government’s vision, which is optimizing the use of renewable energy to ensure the availability of electricity in pursuit of sustainable development in Indonesia.The use of renewable energy to generate electricity,such as geothermal, wind, solar power, and biomass, is only in a small proportion whereas their potential is abundant hence constantly high dependence on fossil energy. In a context of fiscal policy, it shows that the government has made efforts by offering fiscal incentives, however, the fiscal incentives has not been set up in a comprehensive way. Its implementation bears kinds of weakness: impartial, scattered, and lack of coordination. In order to provide comprehensive analysis, quintuple helix perspective is utilized since it covers five different aspects in examining a problematic situation: economic, politics, media, education, and environment to reach sustainable development. The study was conducted through qualitative approach; the data are collected by literature study, in-depth interview, and focus group discussion. The result shows that besides the matter of government coordination, it needs to reconstruct current fiscal policy by considering important aspects, principles of granting fiscal incentives, form, goals/target, and their precondition.